The Effect of Entrepreneurship Education and Creativity on Students’ Entrepreneurial Intention : The Perspective of Effectuation and Cognitive Flexibility Theory - Atrup, Atrup; Diawati, Prety; Syamsuri, Syamsuri; Pramono, Susatyo Adhi; Ausat, Abu Muna Almaududi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to examine the impact of entrepreneurship education and creativity on students' entrepreneurial intention through the perspective of Effectuation Theory and Cognitive Flexibility Theory. The research used a quantitative approach to analyze structural equation modeling (SEM) and Partial Least Square (PLS). Respondents were drawn from 100 university students in Subang Regency, Indonesia, through an online questionnaire. The findings of this study showed positive and significant evidence between entrepreneurship education, creativity, and students' entrepreneurial intention. Through the Effectuation and Cognitive Flexibility Theory principles, students could develop the entrepreneurial attitude, adaptability, and creative thinking necessary to run their own businesses. Entrepreneurship education helps them understand business opportunities, utilize existing resources, and cope with uncertainty.